Helminth parasites of the fourspine stickleback ( Apeltes quadracus (Mitchill)) in Newfoundland - Hanek, George; Threlfall, William (Canadian Journal of Zoology, 1970)
Fifteen specimens of the fourspine stickleback, Apeltes quadracus (Mitchill), caught in Salmonier Arm, near Mitchells Brook, St. Mary's Bay, Newfoundland, were examined for helminth parasites. Three species of monogenetic trematodes (Gyrodactylus avalonia Hanek and Threlfall, 1969; Gyrodactylus cameroni n. sp.; Gyrodactylus canadensis Hanek and Threlfall, 1969), one of digenetic trematodes (Podocotyle atomon (Rudolphi, 1802)), one of Cestoda (Proteocephalus sp.), and one of Nematoda (Cystidicola farionis Fischer, 1798) were recovered.